Beyond literacy and numeracy: cultivating global mindsets in Malaysian education / Siti Nur Dina Mohd Ali ... [et al.] - Mohd Ali, Siti Nur Dina; Zainal Abidin, Dzeelfa; Bazlan, Anis Shahira; Ismail, Mohd Hafizul (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Education for sustainable development (ESD) has been globally informed on the mission to transform learning environments at all levels. As the United Nations Educational, Scientific, and Cultural Organization (UNESCO) has become the leading agency for ESD, this organization is also responsible for the implementation of the framework ESD for 2030. Thus, there are five main ideas highlighted, namely, advancing policy, transforming learning environments, building capacities of educators, empowering and mobilising young people, and accelerating local levels of action (UNESCO, 2024). Teaching and learning should encourage students to be globally prepared in various ways. It is deemed important that education becomes a central part of understanding the surroundings and the world. It should be the means to escape poverty and open the doors to many opportunities. Research done by the Ministry of Education reported that factors contributing to Malaysian students’ dropout rates at schools from the family domain were “poverty, parents of low academic backgrounds, and a lack of interest in their children’s education” (UNICEF, 2023). At the school level, more than 95% of secondary school students at risk of dropping out came from families with a monthly income of less than RM 1,500.